land readjustment method; a solution to Organize of brownfeilds ;case study: the Buick alley of yazd city - mohammad hossien saraei; samaneh iraji (تحقیقات کاربردی علوم جغرافیایی)
The management of land development in the compilation of urban development documents is a very important topic. Failure to pay attention to this necessity, and the course of physical development foreseen for urban areas, make the main goal of the development plan, which improves the quality of housing in urban areas, not being realized. The purpose of this study is to introduce a functional model for land development management in order to guide and manage the urban development flow. To this end, the Land Readjustment Plan (LR) as the selected method of land management in urban areas is introduced and it is possible to perform it in a range of Yazd city. The general research method used in this descriptive-analytic study. The data used in this article collected by the library method as well as the field survey were used and analyzed using ArcGIS software. In this regard, a proposal for the scope of the study was compiled and evaluated before and after the implementation of the plan. The calculation of the distributional index showed that the proposed scheme would give 20% of the profits to the owners in the scope of the study. The conclusion from this study shows that using the Land Readjustment Program as an economic and design tool, planning and redevelopment of undeveloped lands can be done in accordance with urban needs. This planning involves modifying the layout of parts, modifying the network of roads, supplying services and infrastructure of the facility. Thus, the field of realization of urban development plans in these areas was provided. It also provided the basis for the participation of all stakeholder groups through creating the necessary attractions for the groups influencing the implementation of the project.